Analisis Pengaruh Profitabilitas, Ukuran Perusahaan, dan Kebijakan Utang Terhadap Nilai Perusahaan: Studi Empiris pada Property and Real Estate Company yang Terdaftar di Bursa Efek Indonesia - Fierlanda Sheren Ayundha Wardani; Cahyono, Yuli Tri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to test and analyze the influence of profitability, company size, and debt policy on firm value. This research was tested with a sample of 68 property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The sampling method uses purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The findings indicate that profitability, company size, and debt policy have a impact on firm value.